2022
DOI: 10.3389/fmicb.2021.802201
|View full text |Cite
|
Sign up to set email alerts
|

New Insight Into the Interspecies Shift of Anammox Bacteria Ca. “Brocadia” and Ca. “Jettenia” in Reactors Fed With Formate and Folate

Abstract: The sensitivity of anaerobic ammonium-oxidizing (anammox) bacteria to environmental fluctuations is a frequent cause of reactor malfunctions. It was hypothesized that the addition of formate and folate would have a stimulating effect on anammox bacteria, which in turn would lead to the stability of the anammox process under conditions of a sharp increase in ammonium load, i.e., it helps overcome a stress factor. The effect of formate and folate was investigated using a setup consisting of three parallel sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 87 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…Canditatus_Brocadia has been reported to be able to obtain more substrates in low‐nitrogen‐concentration environments through movement. Besides, it has the ability to perceive and respond to nitrogen limitations through inducing changes in transcription, quickly adapt to nitrite limitations and stabilize nitrogen metabolism processes 38 . In addition, Zheng et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canditatus_Brocadia has been reported to be able to obtain more substrates in low‐nitrogen‐concentration environments through movement. Besides, it has the ability to perceive and respond to nitrogen limitations through inducing changes in transcription, quickly adapt to nitrite limitations and stabilize nitrogen metabolism processes 38 . In addition, Zheng et al .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it has the ability to perceive and respond to nitrogen limitations through inducing changes in transcription, quickly adapt to nitrite limitations and stabilize nitrogen metabolism processes. 38 In addition, Zheng et al used an integrated fixed-film activated sludge reactor to treat high-ammonium wastewater and conducted a detailed study on the abundance and diversity of AnAOB and the results indicated that Candidatus_Brocadia preferred to adhere and grow in biofilms, while Candidatus_Kuenenia preferred to grow in suspended sludge. 39 These might be the reasons why the abundance of Candidatus_Brocadia was higher than that of Candidatus_Kuenenia in both R1 and R2.…”
Section: Microbial Community Of Sludge After Operationmentioning
confidence: 99%
“…cMAGs provide comprehensive and accurate information on the metabolic potential and genetic interactions within the anammox community. Unlike previous MAGs (Lawson et al, 2017;Liu et al, 2020;Kallistova et al, 2022) that were affected by discontinuity and contamination, these cMAGs offer a more complete picture of the community. The anammox system was thought to be autotrophic due to the absence of external organic carbon source, but there were still many heterotrophs in this system.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bioreactors to detect and study complex microbial communities has been demonstrated for bacteria from the human microbiome and many environmental systems [ 28 , 29 ]. The bioreactor strongly impacted the community structure of the soil microbiome, as shown in Figure 6 of principal components.…”
Section: Discussionmentioning
confidence: 99%